2016
DOI: 10.1103/physrevlett.116.147203
|View full text |Cite
|
Sign up to set email alerts
|

Static and Dynamical Properties of Antiferromagnetic Skyrmions in the Presence of Applied Current and Temperature

Abstract: Skyrmions are topologically protected entities in magnetic materials which have the potential to be used in spintronics for information storage and processing. However, Skyrmions in ferromagnets have some intrinsic difficulties which must be overcome to use them for spintronic applications, such as the inability to move straight along current. We show that Skyrmions can also be stabilized and manipulated in antiferromagnetic materials. An antiferromagnetic Skyrmion is a compound topological object with a simil… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
528
1
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 573 publications
(546 citation statements)
references
References 26 publications
13
528
1
4
Order By: Relevance
“…This opposition cancels the Magnus force and thus eliminates the unwanted transverse velocity, thereby enhancing skyrmion mobility, as computed by Barker and Tretiakov (2016). Since bulk DMI prevails in antiferromagnetic materials, the prospect for skyrmions in antiferromagnets is potentially more promising.…”
Section: A Experimental Observation Of Antiferromagnetic Texturesmentioning
confidence: 99%
“…This opposition cancels the Magnus force and thus eliminates the unwanted transverse velocity, thereby enhancing skyrmion mobility, as computed by Barker and Tretiakov (2016). Since bulk DMI prevails in antiferromagnetic materials, the prospect for skyrmions in antiferromagnets is potentially more promising.…”
Section: A Experimental Observation Of Antiferromagnetic Texturesmentioning
confidence: 99%
“…37,40 Annihilation of the skyrmions at the edge due to the Magnus force and the drift away from the nanotrack have been studied intensively in recent years. 26,[33][34][35]41,42 Most recently, it has been shown that the edge instability of a thin film with DMI can trigger the creation of skyrmions close to the edge. 43 Additionally, the movements of skyrmions even including the oscillating motion 44 and the gyration 45 are affected by the edges in confined geometries due to their potential force [44][45][46] acting on skyrmions.…”
Section: Introductionmentioning
confidence: 99%
“…Secondly, skyrmions in an antiferromagnet are less sensitive to magnetic fields. Thirdly, they move faster, and in the direction of the charge current (while skyrmions in ferromagnets experience a Magnus force with a significant component perpendicular to their trajectory [19]), which makes it easier to control them [20]. For these reasons, skyrmions have been investigated in many different antiferromagnetic systems, ranging from doped bulk materials [21], Bose-Einstein condensates [22], and various triangular lattice antiferromagnets [23,24] to nanodisks [25].…”
mentioning
confidence: 99%
“…For these reasons, skyrmions have been investigated in many different antiferromagnetic systems, ranging from doped bulk materials [21], Bose-Einstein condensates [22], and various triangular lattice antiferromagnets [23,24] to nanodisks [25]. Isolated AFM skyrmions [26,27], as well as moving skyrmions in AFMs, have been considered theoretically [20,28,29].…”
mentioning
confidence: 99%